2022
DOI: 10.1182/bloodadvances.2021006402
|View full text |Cite
|
Sign up to set email alerts
|

Donor-recipient sex is associated with transfusion-related outcomes in critically ill patients

Abstract: Transfusion of red blood cell (RBC) from female donors has been associated with increased risk of mortality. This study aims to investigate the associations between donor-recipient sex and post-transfusion mortality and morbidity in critically ill patients who received RBC transfusions from either male only donors or from female only donors (unisex-transfusion cases). Survival analysis was used to compare 4 groups: female-to-female, female-to-male, male-to-female, and male-to-male transfusion. Multivariate log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
(52 reference statements)
3
10
0
Order By: Relevance
“…We also observed previously described differences between female and male donors in PZP levels, which is in line with several previous publications that PZP plasma levels are a proxy for sex 15,22,23 . This may be important in the context of sex‐related factors in blood product transfusions 24–26 . In this study, we also show that circulating plasma protein levels correlate with other blood count parameters (e.g., WBC and LBP).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed previously described differences between female and male donors in PZP levels, which is in line with several previous publications that PZP plasma levels are a proxy for sex 15,22,23 . This may be important in the context of sex‐related factors in blood product transfusions 24–26 . In this study, we also show that circulating plasma protein levels correlate with other blood count parameters (e.g., WBC and LBP).…”
Section: Discussionsupporting
confidence: 92%
“…15,22,23 This may be important in the context of sex-related factors in blood product transfusions. [24][25][26] In this study, we also show that circulating plasma protein levels correlate with other blood count parameters (e.g., WBC and LBP). Furthermore, we observed individual plasma protein signatures which are related to the immunological status, including donor-specific immunoglobulin D levels (Figure 2B).…”
Section: Discussionsupporting
confidence: 72%
“…Alshalani et al 1 state in their recent article that the transfusion of red blood cells (RBCs) from female donors to male recipients vs female recipients increases the risk of intensive care unit (ICU) mortality, and that receiving RBCs from female donors is associated with a trend toward acute respiratory distress syndrome. The comparison between male and female recipients of female donor RBCs and its presentation in the visual abstract is misleading.…”
mentioning
confidence: 99%
“…Also, it is likely most females may not be able to donate blood due to childbirth, pregnancy, anemia, and lactation. Some studies have reported an increased risk of mortality among critically ill blood recipients from ever‐pregnant female donors 42–44 . It is however unclear whether this could be a contributory factor to the low patronage of female in blood donation.…”
Section: Discussionmentioning
confidence: 99%